Effects of oat (Avena sativa L.) hay diet supplementation on the intestinal microbiome and metabolome of Small-tail Han sheep - Su, Shaofeng; Wang, Liwei; Fu, Shaoyin; Zhao, Jie; He, Xiaolong; Chen, Qiuju; Belobrajdic, Damien P.; Yu, Chuanzong; Liu, Hongkui; Wu, Haiqing; Han, Pingan; Yang, Bin; et al. (Frontiers in Microbiology, 2022)
Supplementation of the sheep diet with oats (Avena sativa L.) improves animal growth and meat quality, however effects on intestinal microbes and their metabolites was not clear. This study aimed to establish the effect of dietary oat supplementation on rumen and colonic microbial abundance and explore the relationship with subsequent changes in digesta metabolites. Twenty Small-tail Han sheep were randomly assigned to a diet containing 30 g/100g of maize straw (Control) or oat hay (Oat). After 90-days on experimental diets, rumen and colon digesta were collected and microbial diversity was determined by 16S rRNA gene Illumina NovaSeq sequencing and metabolomics was conducted using Ultra-high performance liquid chromatography Q-Exactive mass spectrometry (UHPLC-QE-MS). Compared to Control group, oats increased the abundance of Bacteroidetes and Fibrobacteres as well as known short-chain fatty acid (SCFA) producers Prevotellaceae, Ruminococcaceae and Fibrobacteraceae in rumen(P < 0.05). In rumen digesta, the Oat group showed had higher levels of (3Z,6Z)-3,6-nonadienal, Limonene-1,2-epoxide, P-tolualdehyde, and Salicylaldehyde compared to Control (P < 0.05) and these metabolites were positively correlated with the abundance of cecal Prevotellaceae NK3B31. In conclusion, supplementation of the sheep diet with oat hay improved desirable microbes and metabolites in the rumen, providing insight into mechanisms whereby meat quality can be improved by oat hay supplementation.